Media Take And Give pada Hasil Belajar Materi Ciri-Ciri Khusus Hewan Kelas 3 Pembelajaran IPA di MI Sabilul Mubtadiin Bunut Randegansari - Suryono, Dea Listya Putri Ardana; Kaliwanovia, Tasi’awati Salsa (Prodi Pendidikan Guru Sekolah Dasar, 2026)
The purpose of this study is to describe how the media take and affected the learning outcomes of third grade students in science learning at MI Sabilul Mubtadiin Bunut. This study uses qualitative methods and collects data through observation, interviews, and documentation. The results showed that the Media Take and Give was very effective in the teaching and learning process. Students who previously did not know the specific characteristics of animals can now explain it well. Student responses also show a sense of pleasure and enthusiasm while studying. Based on the study of the Take and Give media, after its use, the ability of class III students in understanding the specific characteristics of animals increases significantly, with results that exceed KKM. Thus, the Media Take and Give makes a positive contribution in helping students understand material related to specific characteristics of animals.